(untitled) (ModaPalavra e-periódico, 2021)
It is increasingly important to present a roadmap for the identification and mapping of mentality and socio-cultural trends and to understand how it contributes to the development of products and services within the scope of trend analysis and strategy. The present panorama of Trend Studies allows generating a basic theoretical-conceptual map that serves as a methodology for organizing sets of ideas and, consequently, practices as a means of systematizing, constructing and confirming the DNA of a trend. This article seeks to explore the intersections between the analysis of culture as a process for the identification of existing mentalities, through a script that facilitates the observation / collection and the systematization of information to present a solid descriptive text of the trends. In addition, the main results of applying trend research to a map of potential products and services in a strategic scope that address this knowledge are highlighted.